Outcomes of percutaneous nephrolithotomy: Comparison of elderly and younger patients - T. Nakamon (2018)
Background and purpose: Percutaneous nephrolithotomy (PCNL) in elderly patients is challenging due to the high prevalence of comorbidity and single kidney. We compared the results and complications of patients who were submitted to PCNL according to age (higher than and lower than 65 years old). Materials and Methods: A total of 61 patients aged more than 65 years old (group I) and 385 patients aged 65 years old or less (group II) were treated with PCNL. PCNL was performed by a standard technique under fluoroscopic guidance. The operative time, length of hospital stay, success rate, auxiliary treatment and complications of both groups were compared. Results: Patients older than 65 years old (group I) had more comorbidities mainly diabetes mellitus, hypertension and higher level of ASA classification (P < 0.001). The success rate was 85.24% and 86.24% of groups I and II, respectively. Four patients (6.56%) of group I and 55 patients (14.29%) of group II needed auxiliary treatment (P = 0.098). Among the complications, only sepsis was significantly higher in group I (6.56% of group I and 1.3% of group II, P = 0.007). The operative time, success rate, hospital stay and complications except sepsis episode did not significantly differ between the two groups. Conclusion: Percutaneous nephrolithotomy is effective and safe in elderly patients even though with more comorbidities. Sepsis is the only more frequent common complication following PCNL in elderly.